2012
DOI: 10.1590/s2176-94512012000400015
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary incisors mesiodistal angulation changes in patients with orthodontically treated anterior superior diastemas

Abstract: Maxillary incisors mesiodistal angulation changes in patients with orthodontically treated anterior superior diastemas original articleObjective: The aims of this study were to describe the patterns of maxillary incisor angulation in patients with upper interincisive diastemas, to evaluate angulation changes with treatment and posttreatment period, and to assess whether there are association between incisor angulation and interincisive diastema relapse. Methods:The sample comprised 30 Class I or Class II patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
4
1
1
Order By: Relevance
“…It is suggested that root parallelism influences the stability after orthodontic closure of anterior diastema 4 , 15 . However, the present results did not confirm any influence of root tip on space relapse ( Table 2 ) and so did the findings presented in a previous study 14 . Additionally, it was found that the slight mesial crown tip of the maxillary incisors occurred during the space closure remained stable posttreatment 14 .…”
Section: Discussioncontrasting
confidence: 93%
“…It is suggested that root parallelism influences the stability after orthodontic closure of anterior diastema 4 , 15 . However, the present results did not confirm any influence of root tip on space relapse ( Table 2 ) and so did the findings presented in a previous study 14 . Additionally, it was found that the slight mesial crown tip of the maxillary incisors occurred during the space closure remained stable posttreatment 14 .…”
Section: Discussioncontrasting
confidence: 93%
“…Nesses casos o ortodontista fica limitado a melhorar a disposição desses espaços. Outro ocorrido frequente é que a movimentação dos incisivos centrais para a mesial pode criar um espaço na distal entre os incisivos central e lateral (MORAIS JF, et al, 2012). Neste quesito, Machado AW (2014) orienta que caso haja algum espaço remanescente, a face distal dos laterais deve ser a área de escolha, pois é a área menos perceptível pelos leigos.…”
Section: Resultsunclassified
“… 14 Inadequate root parallelism at the end of treatment has been also cited as a reason for median diastema relapse. 4 15 However, some mesial inclination of central incisors is preferred. 14 One follow-up study reported relapse of median diastema in 49% patients and found wider initial width of diastema and fremitus of maxillary incisors strongly associated with space opening.…”
Section: Discussionmentioning
confidence: 99%